Promises and Hurdles of Medical Tourism Development in the Russian Federation - Daykhes, Arkady N.; Jakovljevic, Mihajlo; Reshetnikov, Vladimir A.; Kozlov, Vasily V. (Frontiers in Psychology, 2020)
Background Development of medical tourism improves access to healthcare in countries where the necessary medical procedures are not available or accessible to its citizens. In country of destination, medical tourism stimulates economic development and raises the quality of healthcare provided. There are microeconomic and macroeconomic factors affecting the development of medical tourism. Microeconomic factors relate to receivers and providers of healthcare. Macroeconomic factors relate to the government policy being implemented to support the development of medical tourism. This study aims to identify factors affecting the development of medical tourism in Russia. Methodology An expert survey of 36 heads of medical organizations in Russia was conducted to assess the problems that impede development of medical care system to foreign patients in Russia, as well as propose possible solutions. The degree of covariation among experts was calculated using the Kendall concordance coefficient. Results The experts gave consistent evaluation to numerous sets of problems that impede development and proposed concrete measures for the development of inbound medical tourism in Russia. These measures ranged from microeconomic to macroeconomic approaches and were directed towards a holistic and coordinated development of medical tourism within Russia. Conclusion Based on the results, Russia has several micro and macroeconomic competitive advantages and disadvantages in facilitating medical tourism. The study gave set of measures for the development of inbound medical tourism and the promotion of the export of medical services in the Russian Federation, which can be extended to other countries or parties who are seeking to develop medical tourism.